The prevalence of rheumatic heart disease among Grade 10 - 12 learners in the Free State and Northern Cape – Preliminary results of the Wheels-of-Hope Outreach Programme - Smit, F.E.; Botes, L.; Rossouw, S.; Brown, S.C. (SA Heart Journal, 2017)
An outreach programme was initiated to echocardiographically screen Grade 10 - 12 learners, in Central South Africa, for rheumatic heart disease (RHD). Preliminary results, after the screening of 1 015 learners, identifi ed 102 abnormal echocardiograms. The abnormal echocardiograms were reviewed by an echocardiographer and paediatric cardiologist team and 14 pathological conditions were confi rmed in 13 patients. The abnormalities included RHD (n=5), pericardial effusion (n=2), left ventricular hypertrophy (n=2), mitral valve prolapse (n=3), ventricle septal defect (VSD) (n=1) and sub-aorta stenosis (n=1). The benchmark study by McClaren, et al. conducted in Soweto in 1972 (n=12 050, age 2 - 18 years) showed an overall RHD prevalence of 6.9 per 1 000 and 12.2 per 1 000 in the 15 - 18 year old bracket. The highest incidence (19.2/100) was found in Grade 7 learners (age not defined). The preliminary result of this study is 4.9 RHD cases per 1 000 in Grade 10 - 12 learners. This fi nding may indicate an actual decline in the prevalence of RHD in Central South Africa.